The influence of venous blood flow on the retinal ganglion cell complex in patients with primary open angle glaucoma - N. I. Kurysheva; T. N. Kiseleva; P. K. Ryzhkov; A. V. Fomin; N. A. Khodak; T. D. Ardzhevnishvili (Oftalʹmologiâ)
Purpose: To study the influence of venous blood flow on the ganglion cell complex (GCC) in patients with preperimetric and perimetric open angle glaucoma.Methods: 74 patients were included in the research. 59 eyes and 62 eyes were diagnosed with preperimetric and perimetric open angle glaucoma respectively. The mean age was 56.5±10.5 years. 22 (12 female and 10 male) healthy individuals constituted the control group. The ganglion cell complex and retinal nerve fibre layer were evaluated with the help of optical coherence tomography (RTVue-100 OCT, Optovue, Inc., Fremont, CA). Ocular blood flow was measured by Color Doppler Imaging (multifunctional VOLUSON 730 ProSystem). The statistical analysis included correlation between GCC and RNFL thickness in both glaucoma groups.Results: The results showed a statistically significant reduction of venous blood flow velocity in both glaucoma groups compared to the control group. No difference in venous blood flow parameters between two glaucoma groups was found, except resistance index, which was higher in perimetric group in comparison to preperimetric group. A correlation was also obtained between venous blood flow parameters and GCC and RNFL thickness in both glaucoma groups.Conclusion: Early GCC damage in glaucoma might occur due to venous blood flow reduction. This fact may be of great value in understanding glaucoma pathogenesis and search for novel treatment options.